Rare bird documentation form for Greater Scaup at Hickory Grove Lake in 1985 - Martsching, Paulet al (1985)
Rare bird documentation form for a Greater Scaup at Hickory Grove Lake in Story County, IA on November 20, 23, and 27, 1985. Epson - sheet feed